Socio-demographic correlates of booking antenatal care in first trimester among pregnant women in Tanzania. Insights from Tanzania demographic health survey 2022 - Mahiti, Gladys Reuben; Chombo, Suleiman; Luoga, Pankras (Frontiers in Reproductive Health, 2025)
BackgroundIn Tanzania, only 34% of pregnant women come for antenatal care (ANC) in first trimester hence miss an opportunity to be checked and get health advice from the health care workers. However, there is scanty of studies which used national representative data to determine the socio-demographic correlates of problem among pregnant women in Tanzania. Therefore, this study aimed at filling the gap.MethodsThis study analysed secondary data involving a weighted sample size of 4,243 pregnant women aged 15–49 years from the 2022 Tanzania Demographic and Health Survey (TDHS). The analysis adapted a two-level multilevel weighted modified Poisson regression model using Stata 18 software. The dependent variable, “ANC in the first trimester of pregnancy” defined as the binary outcome variable. The independent variables included maternal factors and household factors.ResultsThe two-level multilevel modified Poisson regression indicated that one year increase in age of a mother at first birth results to 2% increase in prevalence of attending ANC in the first trimester (p-value = 0.019). Those in the richest wealth status had 31% higher prevalence of attending ANC in the first trimester compared to counterparts in poorest wealth status (p-value = 0.011). Those with first pregnancy had 23% higher prevalence of attending ANC in the first trimester compared to those with 24–48 months preceding birth interval (p-value = 0.005). Those with more than 48 months preceding birth interval had 28% higher prevalence of attending ANC in the first trimester compared to counterparts who had 24–48 months preceding birth interval (p-value <0.001). Those living in a household with more than 6 members had 32% less prevalence of attending ANC in the first trimester compared to those living in household with 1–4 members (p-value <0.001). Study participants who reported large walking distance to health facility in their residing communities indicated 24% less prevalence of attending ANC in the first trimester (p-value = 0.007).ConclusionANC attendance in the first trimester of pregnancy was significantly associated with wealth index, household size, preceding birth interval, age at first birth and distance to health facility. Programs aiming at increasing early ANC booking should prioritize activities that improve women's livelihoods, particularly those targeting lower socioeconomic and educational groups.